Prevalence of dengue fevers among the patients of different economic status attended at local hospital in Dhaka (Bangladesh Journal of Zoology, 2015)
Blood samples were collected from patients experiencing a febrile illness clinically consistent with dengue infection in IBN SINA hospital, Dhaka. Dengue specific antibodies were detected by using SD Bioline IgM and IgG Rapid Test. Out of suspected cases, 300 patients were confirmed as serologically positive for dengue fever (DF) and 60 patients for dengue hemorrhagic fever (DHF). Larger proportions of serologically positive cases were observed among the females 54% in DF and 60% in DHF than the males 46% in DF and 40% DHF. The highest DF and DHF infected age groups were in between 21 and 30 years, and the common symptoms were fever (100%) and skin rash (100%). The duration of the fever was 5 days which was 26% in DF and 35% DHF.Bangladesh J. Zool. 42(2): 161-168, 2014